A proposed history of permafrost development in Labrador-Ungava - Ives, Jack (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1979)
The recent history of mapping permafrost distribution in Labrador-Ungava is reviewed and an attempt is made to assess the accuracy of the most recent maps. Relationships between ground temperature and other environmental conditions are then discussed. These two introductory sections provide the basis for the main objective of the paper. A hypothesis of permafrost development is elaborated and rests upon two considerations: (1) that much of Labrador-Ungava is underlain by permafrost which is in approximate equilibrium with present-day conditions and that its distribution is largely controlled by vegetation cover rather than regional variations in climate, and (2) that patches of relic permafrost have been found widely throughout the southern section of the peninsula. It is proposed that, following disintegration and melt of the last ice sheet, permafrost developed over wide areas before tree species were able to migrate northwards. As the forest cover-types began to occupy areas comparable to those so occupied today ground thermal characteristics changed. This was caused not only by the direct effects of forest invasion but by the impact of the forest on the winter snow cover. As conditions more nearly approached those prevailing today, degradation of permafrost set in and the present relic patches are air that remains of this process. The hypothesis is supported by recent progress in palynological and vegetational history studies. These demonstrate that a tundra phase existed for 1000 to 2000 or more years between the time of ice sheet disappearance and establishment of the forest cover.